Pengembangan Jiwa Wirausaha Santri Melalui Penguatan Kepemimpinan Berwirausaha Dan Pelatihan Budikdamber Pada Santri Pondok Pesantren Al-Kayyis Bangkalan Madura - Roziana Ainul Hidayati; Farikhah Farikhah (Jurnal Pengabdian Manajemen, 2023)
Santri are known to have independent, simple characters, do not give up easily and are willing to take risks. It is the character of the santri that becomes the capital of an entrepreneurial spirit. The main problem that arises today is the mentality of the entrepreneurial spirit of students. There are still many Islamic boarding schools that do not yet have an entrepreneurship program. In practice, many Islamic boarding schools develop spontaneous entrepreneurial activities. Pondok Al kayyis is a student hostel where all the students are students of Trunojoyo University, Madura. This boarding school consists of Pondok Putri and Pondok Pesantren with a total number of students of approximately 80 students. Budikdamber is an alternative to catfish cultivation that has just been recognized by the students, and this turned out to be very attractive to the students because the ingredients are simple and easy to obtain. Apart from that, budikdamber does not require external land to do so and provides great potential that promises to be used as a business or business. The low cost and fast harvest are the main attraction for the students to try it. The students who have backgrounds in various majors also begin to understand that entrepreneurship does not only require technical skills but also has good leadership skills in entrepreneurship to be successful. Self-confidence, high motivation, always innovative/creative, communicative, solutive and focused are the leadership qualities that must be possessed by successful entrepreneurs.